Compliance, livelihood support, and challenges of the Pantawid Pamilyang Pilipino program of the local government unit - Ramos, Cyril; Verdeprado-Mangga, Richelle; Madrigal, Dennis; Bual, Joel (Technium Social Sciences Journal, 2024)
The 4Ps aim to strengthen the social protection system and reduce poverty in Philippines. Thus, this determined the 4Ps compliance in health and nutrition and education in a component city in Southern Negros Occidental, Philippines as assessed by the implementers and exit beneficiaries relative to designation and beneficiary location. It also profiled the livelihood support among beneficiaries in terms of medium enterprise development and employment facilitation. Likewise, it identified the challenges in the 4Ps implementation. Also, it investigated the difference in the compliance when grouped to demographics. Using the descriptive-comparative design, 151 implementers and 270 beneficiaries responded to the researcher-made questionnaire and checklist. In analysis, mean, standard deviation, and Kruskal Wallis were employed. Meanwhile, the researcher adhered to the Philippine Health Research Ethics Board. Generally, the compliance is very great. Regarding the livelihood support, few beneficiaries received the seed capital of P15,000.00 and employment facilitation fund of P5,000.00. The lack of vehicle, supplies, venue, and inaccessible roads were among the logistics and personnel issues. In knowledge and communication, challenges are on illiteracy, language barrier, lack of training on family and child-related issues. The inability to use ATM cards and pawning were issues too. Meanwhile, there was no difference in the compliance when grouped to demographics. Hence, the findings are instrumental in the continuous improvement of the program’s compliance.